2009
DOI: 10.4049/jimmunol.0802656
|View full text |Cite
|
Sign up to set email alerts
|

TLR2 Deficiency Leads to Increased Th17 Infiltrates in Experimental Brain Abscesses

Abstract: TLR2 plays a pivotal role in recognizing Staphylococcus aureus, a common etiologic agent of CNS parenchymal infections, such as brain abscess. We previously reported that brain abscesses of TLR2 knockout (KO) mice exhibited elevated IL-17 levels, suggesting the presence of an alternative pathway available to respond to S. aureus infection that may involve Th17 cells. Both CD4؉ and CD8 ؉ T cell infiltrates were elevated in brain abscesses of TLR2 KO mice at days 3, 7, and 14 postinfection compared with wild-typ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
54
2
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(62 citation statements)
references
References 90 publications
4
54
2
2
Order By: Relevance
“…The suppressive effect of IFN-g on T H 2 development (46) might be the reason for undetectable IL-4, and the IFN-gmediated inhibition of T H 17 cell differentiation might explain the low levels of IL-17 cells (47)(48)(49). In line with this hypothesis, the TLR2-pathway activated by S. aureus was also associated with reduced proportions of IL-17-producing CD4 + T cells in immune cells surrounding brain abscesses (50). However, in the current study, production of IL-17 may have been supported by high quantities of the proinflammatory cytokine IL-6, possibly together with TGF-b and amplified by high levels of TNF and IL-1b in S. aureus-infected DCs (51).…”
Section: Discussionsupporting
confidence: 69%
“…The suppressive effect of IFN-g on T H 2 development (46) might be the reason for undetectable IL-4, and the IFN-gmediated inhibition of T H 17 cell differentiation might explain the low levels of IL-17 cells (47)(48)(49). In line with this hypothesis, the TLR2-pathway activated by S. aureus was also associated with reduced proportions of IL-17-producing CD4 + T cells in immune cells surrounding brain abscesses (50). However, in the current study, production of IL-17 may have been supported by high quantities of the proinflammatory cytokine IL-6, possibly together with TGF-b and amplified by high levels of TNF and IL-1b in S. aureus-infected DCs (51).…”
Section: Discussionsupporting
confidence: 69%
“…However, the regulatory effects of TLR2 on Th17 cells have appeared to be contradictory in various studies. In pulmonary fungal infection and brain abscess, TLR2 was reported to act as a negative regulator for Th17 cells (24,37), whereas in experimental autoimmune encephalomyelitis, skin inflammation, and tuberculosis infection, TLR2 was reported to have the opposite effect (38)(39)(40). These findings suggest that the specific effect of TLR2 on Th17 cells varies with the type of immune response and depends on the microenvironment of the target tissues.…”
Section: Discussionmentioning
confidence: 66%
“…More recent studies on the role of TLR2 in localized infections in vivo have revealed a much more complex interaction between TLR2 and microbial pathogens. In a murine model of S. aureus brain abscess, TLR2 deficiency was associated with the increased infiltration of IL-17 producing T cells to the lesions [24]. Similarly, in Paracoccidioides brasiliensis infection of the lung, TLR2 À/À mice displayed a Th17 phenotype that was associated with impaired expansion of regulatory CD4 1 CD25 1 Foxp3 1 T cells [25].…”
Section: Discussionmentioning
confidence: 99%